Association of Insulin Resistance and β-cell Function With Bone Turnover Biomarkers in Dysglycemia Patients - Guo, Hui; Wang, Chiyu; Jiang, Boren; Ge, Shaohong; Cai, Jian; Zhou, Ying; Ying, Rong; Zha, Kexi; Zhou, Ji; Wang, Ningjian; Zhu, Chunfang; Cao, Chenyu; et al. (Frontiers in Endocrinology, 2021)
Background The interrelation between glucose and bone metabolism is complex and has not been fully revealed. This study aimed to investigate the association between insulin resistance, β-cell function and bone turnover biomarker levels among participants with abnormal glycometabolism. Methods A total of 5277 subjects were involved through a cross-sectional study (METAL study, http://www.chictr.org.cn, ChiCTR1800017573) in Shanghai, China. Homeostasis model assessment of insulin resistance (HOMA-IR) and β-cell dysfunction (HOMA-%β) were applied to elucidate the nexus between β-C-terminal telopeptide (β-CTX), intact N-terminal propeptide of type I collagen (P1NP) and osteocalcin (OC). β-CTX, OC and P1NP were detected by chemiluminescence. Results HOMA-IR was negatively associated with β-CTX, P1NP and OC (regression coefficient (β) -0.044 (-0.053, -0.035), Q4vsQ1; β -7.340 (-9.130, -5.550), Q4vsQ1 and β -2.885 (-3.357, -2.412), Q4vsQ1, respectively, all P for trend <0.001). HOMA-%β was positively associated with β-CTX, P1NP and OC (β 0.022 (0.014, 0.031), Q4vsQ1; β 6.951 (5.300, 8.602), Q4vsQ1 and β 1.361 (0.921, 1.800), Q4vsQ1, respectively, all P for trend <0.001). Conclusions Our results support that lower bone turnover biomarker (β-CTX, P1NP and OC) levels were associated with a combination of higher prevalence of insulin resistance and worse β-cell function among dysglycemia patients. It is feasible to detect bone turnover in diabetes or hyperglycemia patients to predict the risk of osteoporosis and fracture, relieve patients’ pain and reduce the expenses of long-term cure.